Predictive Value of Skeletal Muscle Mass in Recurrent/Metastatic Head and Neck Squamous Cell Carcinoma Patients Treated With Immune Checkpoint Inhibitors - Arribas, Lorena; Plana, Maria; Taberna, Miren; Sospedra, Maria; Vilariño, Noelia; Oliva, Marc; Pallarés, Natalia; González Tampán, Ana Regina; Del Rio, Luis Miguel; Mesia, Ricard; Baracos, Vickie (Frontiers in Oncology, 2021)
Background: Reduced muscle mass has been associated with increased treatment complications in several tumor types. We evaluated the impact of skeletal muscle index (SMI) on prognosis and immune-related adverse events (IrAEs) in a cohort of recurrent/metastasic (R/M) head and neck squamous cell carcinoma (HNSCC) treated with immune checkpoints inhibitors (ICI). Methods: A single-institutional, retrospective study was performed including 61 consecutive patients of R/M HNSCC diagnosed between July 2015 and December 2018. SMI was quantified using a CT scan at L3 to evaluate body composition. Median baseline SMI was used to dichotomize patients in low and high SMI. Kaplan-Meier estimations were used to detect overall survival (OS) and progression-free survival (PFS). Toxicity was recorded using Common Terminology Criteria for Adverse Event v4.3. Results: Patients were 52 men (85.2%) with mean of age 57.7 years (SD 9.62), mainly oral cavity (n=21; 34.4%). Low SMI was an independent factor for OS in the univariate (HR 2.06, 95%CI 1.14 to 3.73, p=0.017) and multivariate Cox analysis (HR 2.99, 95%CI 1.29 to 6.94, p=0.011). PFS was also reduced in patients with low SMI (PFS HR 1.84, 95%CI 1.08 to 3.12, p=0.025). IrAEs occurred 29 (47.5%) patients. There was no association between low SMI and IrAEs at any grade (OR 0.56, 95%IC 0.20;1.54, p=0.261). However, grade 3-4 IrAEs was developed in 7 patients of whom 3 had low SMI. Conclusions: Low SMI before ICI treatment in R/M HNSCC patients had a negative impact on OS and PFS. Further prospective research is needed to confirm the role of body composition as a predictive biomarker in ICI treatment.